285 Inpatient Management of Medications for Parkinson's Disease. (16th September 2019) - Doyle, Kate; Jonsson, Agnes; O'Sullivan, Ciara; Gallagher, Paul
Abstract: Background: Medication errors during unplanned hospital admissions are common in Parkinson's Disease, often involving late or missed doses. These errors can result in serious complications and loss of function in these patients. Several Parkinson's Disease networks and associations have run campaigns aiming to improve medication administration in hospital. Methods: We reviewed the medical notes and medication charts of 20 patients with Parkinson's Disease admitted through the Emergency Department. Medication charts were reviewed to assess for levo-dopa containing medications. We assessed whether medication dosing and timing was accurately recorded, if medications were administered on time, and if self-management of medication was considered if the patient was capable during the first 48 hours of admission. We measured our findings against standards from NICE guidelines and Parkinson's UK. Results: Only 9 of 20 cases had the times and doses accurately documented on admission. An average of 2.7 doses/patient were missed or delayed in the 48 hour period. Of 152 total doses, 54 (35%) were missed or late. Only 3 out of 20 patients received all their medications on time. Only one out of 20 patients had a documented order to be allowed to self-manage their medication. Conclusion: Medication errors and omissions during unplanned hospital admissions in patients with Parkinson's Disease are unsurprisingly common. Many doctors are unaware of the need to provide alternative routes of delivering levo-dopa for patients with Parkinson's Disease who are fasting or unable to swallow. Patients with Parkinson's Disease are not being empowered to manage their own medication during hospital admission. Educating doctors on the importance of reducing these medication errors, and the existence of the OPTIMAL Calculator to convert the patients' usual medications to alternative preparations, is imperative to improve inpatient management of patients with Parkinson's Disease.